A weight-inclusive approach to applied sport psychology - Derbyshire, A.; Lee, S.; Bejar, M.; Cordova, S.; Crocker, G. (International Journal of Sport and Exercise Psychology, 2025)
Elite-level sport culture places a large emphasis on the pursuit of peak performance at all costs. A common avenue for performance improvement involves the pursuit of leanness, weight loss, and body composition alteration. These practices are based upon weight-centric beliefs and cultural norms that can lead to devastating health consequences for athletes. Sport psychology professionals are uniquely situated to challenge weight-centric norms by implementing weight-inclusive practices and interventions. The purpose of this paper is to educate sport psychology professionals on the dangers of weight-centric practices in sport and provide practical resources for the implementation of weight inclusivity in professional practice. We provide strategies sport psychology professionals can adopt at intrapersonal, interpersonal, and structural levels to promote a weight-inclusive approach to applied sport psychology. Intrapersonal interventions involve seeking education regarding the impacts of weight stigma in both societal and athletic performance contexts. Interpersonal interventions involve the practice of weight inclusivity in professional interactions. We introduced eight principles that can be adopted by sport psychology professionals to make their daily interactions with coaches and athletes more weight-inclusive. Finally, structural interventions centre around the advocacy for and implementation of weight-inclusive policies at the team or athletics programme level. By adopting a weight-inclusive approach, sport psychology professionals can support the physical and mental health of all athletes.